POLITICAL CORRUPTION: POLITICAL AND ECONOMIC STATE CAPTURE IN ETHIOPIA - Gudeta Kebede (European Scientific Journal, ESJ, 2013)
Corruption is an international issue that gets the recognition of the United Nations. International day was assigned to exchange ideas, sharing knowledge, to revitalize the commitment as well as to devise new strategies concerning this securitized matter of all member states. Besides, the UN provided convention that has been ratified by states of the world. Ethiopia is one of those which have signed this convention and currently institutionalized the ‘cosmetic’ anti-corruption practice. Yet, things have a different scenario in Ethiopia; its political systems are deficient in democratic power sharing formula, check and balance, accountable and transparent institutions and procedures. These deficits of democracy are clearly observed when one compares the significant steps of the country’s transition from its authoritarian legacy to the current ‘rhetoric’ good governance experience of the country. The artificial nature and the failure of the country's transformation to democratic governance and its legacy to the deficit of the political system open the door to corruption and facilitated the fertile breeding ground for this political gangrene. This article argued that the perpetuation of political corruption on the part of the incumbent government in Ethiopia, significantly aborted the country’s democratization process, eroded the country’s rule of law, prevail a politicization of the country’s civil service system, as well as the monopolization of the country’s economy.